First searches for axions and axionlike particles with the LUX experiment - Akerib,DS; Alsum,S; Aquino,C; Araujo,HM; Bai,X; Bailey,AJ; Balajthy,J; Beltrame,P; Bernard,EP; Bernstein,A; Biesiadzinski,TP; Boulton,EM; et al. (Physical Review Letters, 2017)
The first searches for axions and axionlike particles with the Large Underground Xenon experiment are presented. Under the assumption of an axioelectric interaction in xenon, the coupling constant between axions and electrons gAe is tested using data collected in 2013 with an exposure totaling 95 live days ×118  kg. A double-sided, profile likelihood ratio statistic test excludes gAe larger than 3.5×10−12 (90% C.L.) for solar axions. Assuming the Dine-Fischler-Srednicki-Zhitnitsky theoretical description, the upper limit in coupling corresponds to an upper limit on axion mass of 0.12  eV/c2, while for the Kim-Shifman-Vainshtein-Zhakharov description masses above 36.6  eV/c2 are excluded. For galactic axionlike particles, values of gAe larger than 4.2×10−13 are excluded for particle masses in the range 1–16  keV/c2. These are the most stringent constraints to date for these interactions.